Reflexão epistemológica e memorialística: uma experiência na formação continuada de professores de ciências - SILVA, Paulo Sérgio Araújo da (2007)
This work is about the investigation developed during the process of continual formation of science teachers (from the subjects of Chemistry, Biology, Physics and Primary School's Sciences) in a public University. This work consists in a narrative research in which we seek to comprehend the relations what kind of relations there are between epistemological reflection and teaching formation. We have been looked for, in particular, to investigate what kind of reflections the subject-teachers build up from the introduction of discussions that concern to the process of production, validation and social appropriation of the scientific knowledge and the relations they set up with their stories of performance and personal and professional formation. With this aim a process of um-alienation of himself was stimulated the teachers, asking them to produce memorialists narratives in which they related some aspects concerning to the epistemological questions during, closely, the two months whose lasted the continual formation. Farther on the memorialists narratives, that have been produced in the end of the course, other registers were used, also, like source of investigation: the transcriptions of the audio registers from the weekly meetings between the lecturer and the teachers; the answers for a questionnaire applied on the first contact with the teachers and the field notes produced during the meetings. The analysis of the entirety of the materials produced is a sign that the recursive action of the memory, stimulated by the epistemological discussions on the present, has raised the teacher's reflections in four mainly dimensions: Ethic-political, curricular, methodological and affective. Such these dimensions unchained some examination on the pedagogical practice of the teachers involved in the study. This led them to think about the nature and the origins of the knowledge they have been taught and validated in the school. Such revision resulted on the awakening of other ways to think about what to teach, why and how to teach sciences and about the valorization not only of scientific knowledge, but also of other knowledges in order to build the scholar curriculum.